2023
DOI: 10.3390/bioengineering10060697
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peripheral Vision on Manual Reaction Time Using Fitlight Technology for Handball, Basketball and Volleyball Players

Dana Badau,
Alina Mihaela Stoica,
Marin Florin Litoi
et al.

Abstract: The purpose of the research was to identify the impact of peripheral (unilateral and bilateral) vision on manual reaction time to visual stimuli in handball, basketball and volleyball players by implementing a 6-week experimental program of specific exercises and some adapted tests using Fitlight technology. The research included 412 players (212 male—51.5%; 200 female—48.5%) from three team sports: basketball—146 (35.4%), handball—140 (40%) and volleyball—126 (30.6%). The experimental program carried out over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…As in the present study, one of the most commonly used devices to assess players' motor skills and cognitive processes is the FITLIGHT Trainer TM [33][34][35][36][37][38]. The device finds its application both as a measurement tool and as a tool used in training to monitor the development of athletes in terms of specific motor parameters.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As in the present study, one of the most commonly used devices to assess players' motor skills and cognitive processes is the FITLIGHT Trainer TM [33][34][35][36][37][38]. The device finds its application both as a measurement tool and as a tool used in training to monitor the development of athletes in terms of specific motor parameters.…”
Section: Discussionmentioning
confidence: 94%
“…The device finds its application both as a measurement tool and as a tool used in training to monitor the development of athletes in terms of specific motor parameters. Using the FITLIGHT Trainer TM , studies have shown a beneficial effect of peripheral vision training in basketball, volleyball, and handball players in improving the time of manual reaction to visual stimuli [33]. Reaction speeds, agility, and dribbling skills were significantly improved in a group of youth basketball players after FITLIGHT reactive agility training [34].…”
Section: Discussionmentioning
confidence: 99%
“…For basketball players, reaction speed and peripheral vision play a major role in-game actions. For both genders, better values and progress are found in reaction times for bilateral visual stimuli (30 s), compared to similar handball and volleyball groups (Badau et al, 2023). Our results on the influenc of basketball on speed indicate a positive rating for almost 60% of those surveyed, with only 15% indicating the opposite.…”
Section: Discussionmentioning
confidence: 41%